Spirituality and Anxiety In Elderly With Hypertension - Yusuf Waliyyun Arifuddin; Whisky Fredika; rudiyanto rudiyanto; Fany Anitarini (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Anxiety is an emotional condition that causes discomfort which is characterized by feelings of worry, anxiety and fear so that it can interfere with life. One of the factors that cause anxiety in the elderly is spiritual activity. The higher the spiritual level of the elderly, the lower the level of anxiety will be. This study aimed to determine the correlation between spiritual level and anxiety in the hypertensive elderly. The design of this study was correlational with a cross sectional approach. The sample was 31 respondents. The sampling technique used was purposive sampling and the statistical test used was Rank Spearman. The measuring instruments used were the Daily Spiritual Experience Scale (DSES) and Geriatric Anxiety Scale (GAS) questionnaires. The research results showed that most of the respondents were at a moderate spiritual level (58.1%) and most of the respondents were at a moderate level of anxiety (71.0%). The Spearman Rank test result showed a Significance (2-tailed) result of 0.000 (ρ < 0.05). So, it can be concluded that there was a significant correlation between Spiritual and Anxiety Level with a very strong relationship. The higher the spiritual level, the lower the level of anxiety felt. Therefore, spiritual activities such as getting closer to God, participating in studies, reading holy books or holy Qur’an that are believed to be, and having a good relationship with the surrounding environment are very beneficial for the elderly to control their anxiety, especially for the elderly who have chronic diseases.